Linfohistiocitosis hemofagocítica por Histoplasma capsulatum en paciente con trasplante renal - Alejandro Camargo-Salamanca (Infectio, 2020)
Hemophagocytic Lymphohistiocytosis (HLH) induced by Histoplasma capsulatum is a rare entity who is characterized by phagocytosis of hematopoietic cells by tissue macrophages. A 44-year-old male patient with kidney transplantation was admitted to our ambulatory service with fever. Initially, we performed a thick drop test who was positive for P. vivax, so antimalarial therapy was initiated. Patient then progressed to multiple organ dysfunction after 2 days of treatment. Thus, a reference center went back over the blood smear which revealed the presence of yeast cells H. capsulatum within polymorphonuclear cells. This result was confirmed by an immunodifussion assay. Despite of antifungal treatment, patient passed away. The diagnosis for unusual microorganism with unspecific clinical presentation could be a challenge in immunosupressive patients.